Urologic practice patterns of pediatricians: a survey from a large multisite pediatric care center - Stewart, Courtney A.; Jeong Kim, Soo; Phillips, Daniel; Bhatia, Vinaya; Janzen, Nicolette; Gerber, Jonathan A. (Frontiers in Pediatrics, 2023)
Objective: To evaluate the practice patterns of pediatricians as they relate to common urologic concerns. Materials and Methods: An anonymous 15-question survey was created and distributed to all pediatricians at our institution, a large multisite care center. This study was deemed exempt by the institutional review board. Results: 55 of the 122 (45%) providers queried responded. 93% of the participants were female, and 7.3% were male. 55% recommended testicular self-examination at adolescence, while 39% did not recommend at any age. 78% stated that they were "Fairly confident" in the exam for undescended testicle. One-third referred patients with UDT to a subspecialist upon recognition at birth, 13% at 3 months of age, and 28% at 6 months of age. 10% reported obtaining a VCUG after the first febrile UTI, 26% after the second, and 36% only if there were abnormal findings on renal ultrasound. 28% of providers reported that they refer to pediatric urology after the initial febrile UTI. 19% provided antibiotics for UTI symptoms alone with negative urinalysis and urine culture. Conclusions: Despite established guidelines, practice patterns varied among pediatricians.Pediatricians typically followed the AAP's guidelines regarding VCUGs (62%), with only a few adhering to urologic recommendations (9%). Despite the consistency between with AAP and AUA guidelines regarding the age at which to refer a patient for cryptorchidism, about 70% of practitioners referred patients too early or too late. Harmonized, consolidated guidelines between pediatricians and pediatric urologists would improve patient care and efficiency of the healthcare system.